Molecular detection of Histoplasma capsulatum in insectivorous and frugivorous bats in Southeastern Brazil - Dos Santos, Bruna [UNESP]; Langoni, Helio [UNESP]; da Silva, Rodrigo Costa; Menozzi, Benedito Donizete [UNESP]; Bosco, Sandra de Moraes Gimenes [UNESP]; Paiz, Laís Moraes; Augusto, Livia Carla Ramos; Richini-Pereira, Virgínia Bodelão (Oxford University Press (OUP), 2018)
Bats are considered to play a significant role in the epidemiology of histoplasmosis, worldwide. We investigated the occurrence of H. capsulatum in lung samples from 89 bats, from urban areas in Southeastern Brazil, using nested PCR based on ribosomal DNA. Fungal DNA was detected in 31/89 samples (34.8%), of which 13/31 were Molossids (41.9%), 4/31 Eumops spp. (12.9%), 2/31 Artibeus lituratus (6.5%), and 12/31 others (38.7%). This is the first report of natural infection by H. capsulatum in A. lituratus in Southeastern Brazil, which reinforces the importance of these synanthropic animals in the epidemiology of histoplasmosis in urban areas.